Hunting success of lions affected by the moon’s phase in a wooded habitat - Preston, E; Johnson, P; Macdonald, D; Loveridge, A (Wiley, 2019)
Variation in moonlight affects foraging, hunting and vigilance behaviours in many nocturnal species. Here, we explore the effect of moonlight on the movement and hunting behaviour of African lions. Previous studies found bright moonlight is associated with reduced hunting success; however, those studies were largely undertaken in open habitats where predators are easily seen by prey species on moonlit nights. In this study we explored whether moonlight affected hunting behaviour and success in a largely wooded environment. Measures of short-term lion movements (distance moved, displacement, and path tortuosity) derived from GPS telemetry data were used as indicators of movement behaviour. Field observations of belly distension were used to assess recent food intake. Lions had greater belly distension (indicating feeding success) on dark nights. However, this change in feeding success was not reflected by lion movement patterns – there was no evidence that these changed across moon phases. There was no evidence that lions used more covered habitats on brighter nights to facilitate concealment.